La desintegración familiar y la agresividad en los niños y niñas de educación inicial y primer año de educación general básica del Cendro Educativo Dr. Alfredo Pérez Guerrero del cantón Santa Rosa periodo lectivo 2012-2013. - Cruz Suriaga, Zaida Belén (2013)
For this reason, we thought it important and necessary to address the issue: family disintegration and aggression in children Early Childhood Education and First General Education Basic Education Center Dr. Alfredo Perez Guerrero Santa Rosa Canton 2012-2013 school period , the same as not being new, requires current contributions, respect for the problems observed on campus.